2021
DOI: 10.1088/1748-605x/abdbdc
|View full text |Cite
|
Sign up to set email alerts
|

Beta-tricalcium phosphate promotes osteogenic differentiation of bone marrow-derived mesenchymal stem cells through macrophages

Abstract: Macrophages are vital regulators of skeletal remodeling and osseous repair. Beta-tricalcium phosphate (β-TCP) is a synthetic ceramic biomaterial that has shown promise as bone substitute. However, whether and how β-TCP affects osteogenesis-related responses of macrophages has rarely been studied. The aims of this study were to explore (a) the effects of β-TCP on osteogenic differentiation of bone marrow-derived mesenchymal stem cells (BMSCs) co-cultured with macrophages and (b) on macrophage polarization as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 60 publications
3
10
0
Order By: Relevance
“…The concentrations of Ca and P ions (Ctrl, 1/32, 1/64, and 1/128) were detected by ICP-AES, as shown in Figure 1A . The concentrations of Ca were 66.20 ± 1.53, 65.37 ± 0.81, 64.26 ± 0.97, and 65.79 ± 1.26 mg/L in Ctrl, 1/32, 1/64, and 1/128 dilutions, respectively, while the concentrations of P were 32.05 ± 1.64, 29.96 ± 0.65, 29.80 ± 0.96, and 30.99 ± 0.19 mg/L, respectively, which were consistent with a previous study and showed no significant difference in the concentrations of Ca and P[ 27 ]. The pH values were 7.353 ± 0.012, 7.343 ± 0.012, 7.427 ± 0.009, and 7.427 ± 0.021, respectively ( Figure 1B ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The concentrations of Ca and P ions (Ctrl, 1/32, 1/64, and 1/128) were detected by ICP-AES, as shown in Figure 1A . The concentrations of Ca were 66.20 ± 1.53, 65.37 ± 0.81, 64.26 ± 0.97, and 65.79 ± 1.26 mg/L in Ctrl, 1/32, 1/64, and 1/128 dilutions, respectively, while the concentrations of P were 32.05 ± 1.64, 29.96 ± 0.65, 29.80 ± 0.96, and 30.99 ± 0.19 mg/L, respectively, which were consistent with a previous study and showed no significant difference in the concentrations of Ca and P[ 27 ]. The pH values were 7.353 ± 0.012, 7.343 ± 0.012, 7.427 ± 0.009, and 7.427 ± 0.021, respectively ( Figure 1B ).…”
Section: Resultssupporting
confidence: 91%
“…Therefore, these two elements of β-TCP promote bone regeneration. Herein, we detected the release of calcium and phosphorus, which was also reported in a previous study[ 27 ]. No significant difference existing among the four groups was possibly linked to the precipitation of calcium phosphate.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, β‐TCP further enhanced PEGS membrane‐induced M2 polarization, which resulted in significant M2 macrophage infiltration in defects treated with the PEGS/β‐TCP membrane at earlier stages. This finding was supported by the study of Zheng et al., [ 26 ] which demonstrated that β‐TCP extract upregulates M2 polarization by regulating the Wnt signaling pathway. Following the increase in M2 macrophages, the PEGS/β‐TCP membrane induced higher expression of VEGF, IGF‐1, BMP2, and TGF‐β1 than did the PEGS membrane.…”
Section: Discussionsupporting
confidence: 64%
“…In another study, scientists transplanted TCP particles loaded with histone methyltransferase enhancer of zeste1 (EZH1) into animal models and they found that the proportion of M 2 Mϕs was significantly increased compared with that of in the control group [ 44 ]. Moreover, another study recently has shown that β-TCP particles had the ability to enhance the osteogenic differentiation of BMSCs by inducing the polarization of Mϕs and regulating the Wnt signaling pathway [ 185 ]. However, the function of TCP particles on bone immune system is still in dispute.…”
Section: The Prospects For the Crosstalk Between Mϕs And Bmscs In Bon...mentioning
confidence: 99%